MiR319a/TCP module and DELLA protein regulate trichome initiation synergistically and improve insect defenses in Populus tomentosa. Issue 3 (12th May 2020) - Fan, Di; Ran, Lingyu; Hu, Jian; Ye, Xiao; Xu, Dan; Li, Jianqiu; Su, Huili; Wang, Xianqiang; Ren, Sha; Luo, Keming
Summary: Trichomes are specialized epidermal cells that contribute to plant resistance against herbivores. Their formation is controlled precisely by multiple genetic and environmental signals. Previous studies have shown that microRNA319 (miR319) and gibberellin (GA) signaling are involved in trichome development in Arabidopsis, but little is known about their interaction between these factors. Here we reported that the miR319a/TEOSINTE BRANCHED/CYCLOIDEA/PCF (TCP) module participates in trichome initiation synergistically with GA signaling in Populus tomentosa . We demonstrated that overexpression of miR319a decreased transcription levels of its targeted TCP s and significantly elevated leaf trichome density in transgenic poplar, resulting in decreasing insect herbivory. Conversely, repressing miR319a by short tandem target mimics (STTM) elevated TCP expression levels and decreased trichome density in transgenic plants. The trichome phenotype of 35S:miR319a plants could be abolished by introducing a miR319a‐resistant form of TCP19 . Furthermore, the miR319a‐targeted TCP19 interacted directly with REPRESSOR OF ga1‐3 (RGA), a downstream repressor of GA signaling. TCP19 and RGA synergistically inhibited the GLABROUS1 (GL1)‐induced expression of trichome marker gene GLABRA2 ( GL2 ), thereby repressing leaf trichome initiation. Our results provide an insight into the molecular mechanism by which miR319/TCP19 module and GA signaling coordinated regulating trichome initiation in P. tomentosa .